The Relationship Between Online Gamification Performance Score With Body Mass Index Of Overweight Nursing Students During Covid-19 Pandemic - Hipona, Jocelyn; Tuazon, Alicia; Martin, Joan; Cabading, Marlyn Lumitap (Journal Of Nursing Practice, 2021)
Background: Online intervention platforms are effective for gathering data especially in this pandemic crisis we are currently experiencing, and it can help healthcare practitioners on future innovations. Numerous studies also show the importance of online nursing intervention platforms in the promotion of health on overweight and obese adults, by way of social media.Purpose: This study aimed to determine relationship between online gamification performance score with body mass index of overweight nursing students during covid-19 pandemic.Methods: The total number of participants were 60 based on the type of research employed, computation of BMI and proper assessment before the study was conducted to make sure that participants meet the inclusion criteria.Results: Evidence from this study illustrates that the performance assessment score in online gamification has almost no relationship with changes in the body mass index.Conclusion: There are no changes in the body mass index of the overweight nursing students whether exposed to usual daily activities or online gamification. Data indicates that the four (4) week intervention to online gamification does not have relational changes on body mass index